INTEGRATION OF HR-MARKETING AND THE SYSTEM OF MARKETING COMMUNICATIONS IN THE PROCESS OF ENTERPRISE RELOCATION: AN ORGANIZATIONAL AND ANALYTICAL APPROACH - US, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the organizational and analytical aspects of integrating HR marketing and marketing communications in the enterprise relocation process. In the context of Ukraine’s full-scale war, many companies are forced to relocate their production facilities and offices, which significantly affects marketing activities, internal and external communication, and human resource management. The study emphasizes that successful relocation requires the alignment of internal communications with external marketing strategies, ensuring employee engagement, maintaining brand reputation, and preserving operational stability. The research provides a theoretical and analytical overview of HR marketing as a tool for employer branding, staff motivation, and talent retention during organizational transformation. It analyzes the role of marketing communications in coordinating interactions between internal departments, clients, partners, and local communities. The paper proposes an integrated organizational-analytical model (3C-model: Communication–Coordination–Culture) for ensuring effective information flows and consistent corporate culture in relocated enterprises. The study is based on an analysis of recent Ukrainian and international publications, including research on employee satisfaction, government support mechanisms, and strategic marketing adaptation during relocation. The findings demonstrate that HR marketing and coordinated communication systems are critical for enterprise resilience, competitiveness, and employee loyalty during periods of significant operational change. The article contributes to the theoretical understanding of integrated marketing and HR strategies and provides practical recommendations for enterprises undergoing relocation, highlighting the importance of analytics, organizational coordination, and strategic employer branding in ensuring sustainable business performance.
Keywords: HR marketing; marketing communications; enterprise relocation; organizational and analytical support; employer branding; corporate communication strategy; employee engagement; business transformation